Quality and Tool Stability Improvement in Turning Operation Using Plastic Compliant Damper. (1st September 2022) - Sathyapriya, G.; Natarajan, U.; Sureshkumar, B.; Navaneethakrishnan, G.; Palanisamy, R.; Bajaj, Mohit; Sharma, Naveen Kumar; Kitmo,
Abstract : The major hindrance for any production industry in obtaining higher yield is the lack of achieving full material removal rate in the machine tools. If achieved, the surface quality of the machined works will be compromised. An attempt was made in this work to reduce the compromise of surface finish by integrating a plastic compliant damper that is capable of reducing the effects of unwanted vibrations generated during the machining process. The damper is designed to degenerate the effects of vibration and thereby improve product finish. It is made of acrylonitrile butadiene styrene by fused deposition modelling (an additive manufacturing technique). Measuring the vibration and cutting force is indirectly related to finish in product and tool wear rate. The stability of tool is improved greatly by the new compliant damper possessing displacement resistance. The effect of variation in cutting conditions on the performance of conventional rubber damper and plastic compliant damper was analyzed. The highest speed, feed rate, and depth of cut of 540 rpm, 0.02 mm/s, and 1.5 mm, respectively, found to be cutting condition at which imparted minimum surface roughness values of 2.80  μ m and 0.52  μ m with conventional rubber damper and plastic compliant damper, respectively. The speed and feed rate and depth of cut are found to be important parameters while studying surface roughness. The peak surface roughness is reduced by 48% by using the proposed compliant damper.